EGFR-targeting RNase A-cetuximab antibody-drug conjugate induces ROS-mediated apoptosis to overcome drug resistance in KRAS mutant cancer cells - Bita Jafary; Mostafa Akbarzadeh-Khiavi; Hamed Farzi-Khajeh; Azam Safary; Khosro Adibkia (Scientific Reports)
Abstract Antibody-drug conjugates (ADCs) are an emerging strategy in cancer therapy, enhancing precision and efficacy by linking targeted antibodies to potent cytotoxic agents. This study introduces a novel ADC that combines ribonuclease A (RNase A) with cetuximab (Cet), an anti-EGFR monoclonal antibody, through a polyethylene glycol (PEG) linker (RN-PEG-Cet), aimed to induce apoptosis in KRAS mutant colorectal cancer (CRC) via a ROS-mediated pathway. RN-PEG-Cet was successfully synthesized and characterized for its physicochemical properties, retaining full enzymatic activity in RNA degradation and high binding affinity to EGFR. In KRAS mutant SW-480 cells, RN-PEG-Cet significantly reduced cell viability at lower doses, with an IC50 of 11.7 µg/mL at 72 h. Compared to free Cet, RN-PEG-Cet demonstrated a ~ 2-fold increase in apoptosis and a ~ 3.5-fold increase in ROS production. The conjugate also disrupted the Nrf2/Keap1 pathway, with a significant upregulation of Keap1 (FC = 3.7, p ≤ 0.01) and downregulation of Nrf2 (FC = 3.3, p < 0.01), highlighting its role in impairing antioxidant defenses and promoting ROS-mediated cytotoxicity. These findings emphasize the potential of RN-PEG-Cet as a novel therapeutic approach for KRAS mutant CRC, offering superior apoptosis induction and targeted cytotoxicity compared to conventional therapies. This ADC could represent a new strategy for improving CRC treatment outcomes by effectively overcoming resistance mechanisms.